Morphing structure actuation - Wu, Shuli. (2011)
Because of superior benefits of morphing aircraft, interest in morphing structure has increased in the past few decades. The concept of a morphing wing able to adapt itself for different aerodynamic characteristics during flight is are what aircraft research is mostly heading to. This project mission is to demonstrate an actuation mechanism for the morphing wing structure design which is capable of extending the wing fuselage length along the leading edge with a smooth motion.